The Transition from Implementing the K-13 Curriculum to the Merdeka Belajar Curriculum in Elementary Schools - M. Ubaidillah Ridwanulloh; Ayu Fransiska Wulandari; Tina Nur Fitriana; Agiel Muhammad; Yulianti Yusal; Fitria Lestari (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
his research aims to describe the curriculum management implementation process at the primary school level. The phenomenon of changing times is unavoidable, especially after the COVID-19 pandemic, which has necessitated rapid changes in all aspects of human life, including education. Therefore, there has been a curriculum change in the Republic of Indonesia with the emergence of the